Behind the Curtain: In Silico and In Vitro Experiments Brought to Light New Insights into the Anticryptococcal Action of Synthetic Peptides - Tawanny K. B. Aguiar; Nilton A. S. Neto; Romério R. S. Silva; Cleverson D. T. Freitas; Felipe P. Mesquita; Luciana M. R. Alencar; Ralph Santos-Oliveira; Gustavo H. Goldman; Pedro F. N. Souza (MDPI AG, 2023)
Cryptococcus neoformans is the pathogen responsible for cryptococcal pneumonia and meningitis, mainly affecting patients with suppressed immune systems. We have previously revealed the mechanism of anticryptococcal action of synthetic antimicrobial peptides (SAMPs). In this study, computational and experimental analyses provide new insights into the mechanisms of action of SAMPs. Computational analysis revealed that peptides interacted with the PHO36 membrane receptor of C. neoformans. Additionally, ROS (reactive oxygen species) overproduction, the enzymes of ROS metabolism, interference in the ergosterol biosynthesis pathway, and decoupling of cytochrome c mitochondrial membrane were evaluated. Three of four peptides were able to interact with the PHO36 receptor, altering its function and leading to ROS overproduction. SAMPs-treated C. neoformans cells showed a decrease in scavenger enzyme activity, supporting ROS accumulation. In the presence of ascorbic acid, an antioxidant agent, SAMPs did not induce ROS accumulation in C. neoformans cells. Interestingly, two SAMPs maintained inhibitory activity and membrane pore formation in C. neoformans cells by a ROS-independent mechanism. Yet, the ergosterol biosynthesis and lactate dehydrogenase activity were affected by SAMPs. In addition, we noticed decoupling of Cyt c from the mitochondria, which led to apoptosis events in the cryptococcal cells. The results presented herein suggest multiple mechanisms imposed by SAMPs against C. neoformans interfering in the development of resistance, thus revealing the potential of SAMPs in treating infections caused by C. neoformans.